Synthesis, Characterization, and Recyclability of a Functional Jute-Based Geopolymer Composite - Alshaaer, Mazen (Frontiers in Built Environment, 2021)
This study describes the properties of geopolymer composites reinforced with bidirectional jute fibers. Their flexural strength is 12 MPa, four times higher than the strength of non-reinforced reference geopolymers. The bidirectional jute-reinforced geopolymer composite (JGC) is characterized by ductility and high elongation as well as strain hardening with a modulus of 66 MPa. It is found that the introduction of bidirectional jute fibers in the geopolymer matrix increases the adsorption capacity of Cr ions from 2.7 mg/g up to 6.4 mg/g (pH=5). The JGC can be recycled by grinding the material, and then using both the geopolymer material and the jute micro-fibers as filler and reinforcement for a new geopolymer matrix. The micro-fiber jute-reinforced composite obtained showed noteworthy mechanical properties, with strength three times higher than that of the reference material, when 2.5 wt% filler was added. Moreover, the ductility of the composite can be substantially enhanced by increasing (up to 10 wt%) the proportion of recycled jute-based geopolymer filler. These composites are therefore proposed as candidate materials for applications in the context of a circular economy.